Budaya Religius Dalam Pembentukan Karakter Peserta Didik Di SMP Islam Ulul Albab Nganjuk - Misfaf Abdul Azis; Ahmad Masrukin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
This paper is to examine the religious culture of the character formation of students in Ulul Albab Islamic Middle School Nganjuk. This study departs from two research questions.